2019
DOI: 10.23937/2378-3001/1410083
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Oxidative Stress, Inflammation, and Glutamate in Ototoxicity, and their Attenuation by Simultaneous Activation of Nrf2 and Elevation of Antioxidant Compounds

Abstract: Diverse groups of ototoxic agents and gene mutation induce hearing disorders. Several studies showed that increased oxidative stress, inflammation, and glutamate are involved in the initiation and progression of hearing disorders. Therefore, reducing these biochemical defects before and after exposure to ototoxic agents may prevent and improve the management of hearing loss. Previous studies with a single agent have yielded variable benefits in hearing disorders. This review briefly presents evidence for the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 126 publications
(163 reference statements)
0
2
0
Order By: Relevance
“…Inflammation caused by bacterial infection has been reported to exacerbate AG-enhanced toxicity in the cochlea due to the upregulation of the AG-permeable cation channel TRPV1 [47]. In addition, pre-inflammatory cytokines account for this toxicity enhanced by cisplatin, another toxic reagent in cell-based and animal studies [48,49], thus highlighting the importance of inflammation in hearing disorders originating from various causes, such as noise and aging [50]. In this study, we demonstrated that DKB122 inhibits the expression of chemokine-and interleukin-related genes by regulating the nuclear translocation of NF-κB in auditory blast cells.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation caused by bacterial infection has been reported to exacerbate AG-enhanced toxicity in the cochlea due to the upregulation of the AG-permeable cation channel TRPV1 [47]. In addition, pre-inflammatory cytokines account for this toxicity enhanced by cisplatin, another toxic reagent in cell-based and animal studies [48,49], thus highlighting the importance of inflammation in hearing disorders originating from various causes, such as noise and aging [50]. In this study, we demonstrated that DKB122 inhibits the expression of chemokine-and interleukin-related genes by regulating the nuclear translocation of NF-κB in auditory blast cells.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study, exposure to noise (104 dB) and silver nanoparticles (100 mg/kg) increased oxidative stress in the serum (Zahra et al 2022). Noise exposure can cause lipid peroxidation and decrease critical antioxidants such as glutathione through metabolic pathways, including an excessive increase of glutamate and calcium ions, as well as the production of free radicals, leading to the onset and progression of hearing loss (Kopke et al 2007, Prasad 2019). Some other studies indicated that exposure to high noise intensity (115 dB, 5 hr) decreased the total antioxidant capacity of serum and increased reactive nitrogen species in the cochlea of guinea pigs (Diao et al 2003).…”
Section: Oxidative Changesmentioning
confidence: 95%